Walking and expressing the city collectively, a teaching-learning experience in the Postgraduate Program in Architecture and Urbanism - Hirao , Hélio; Tarocchi , Carolina Silva; Frascareli , Marina Biazotto (Revista Nacional de Gerenciamento de Cidades, 2024)
The article experiments with methodologies for apprehending and cognizing city spaces. It shares the development of a discipline in the Postgraduate Program in Architecture and Urbanism at Universidade Estadual Paulista (Unesp) with the theoretical-methodological discussion complemented by the practice of Wandering and Cartography in a common space in the neighborhood of Vila Colonial in the city of Bauru, SP. It distances itself from the traditional representational methods of reading the city and approaches to those that express the subjective city, the traversal through the affections of bodies and environments in order to make existential territories visible and thus think about and build a city for and with the people who inhabit the place. In this methodological procedure of wandering, it recognizes the resistance to the functionalist and productivist city and expresses, through affective cartographies, which are still in the process of construction, a visual language, as a research tool that makes it possible to report on the real city.